Renal Denervation A New Approach to Treatment of Resistant Hypertension - Heuser, Richard R.; Schlaich, Markus; Sievert, Horst (Springer London : Imprint: Springer, 2015)
This book examines renal pathophysiology and the rationale for renal denervation (RDN), a minimally invasive, endovascular catheter based procedure using radiofrequency ablation for the treatment of resistant hypertension, a leading cause of morbidity and mortality in western civilization. In addition, the possible long term benefits and risks of this new therapy are discussed together with a description of the myriad of currently available devices and approaches involved in the evolution of this treatment. Lastly, the book focuses on the cost effectiveness of renal denervation and future directions for other possible benefits.  Written by world renowned leaders in the field, Renal Denervation will be of immediate use to cardiologists, nephrologists and urologists as well as allied health professionals, device companies and anyone working in this field.  .